Supplementation of Fermented Moringa Leaves in Feed on Blood Glucose of Striped Catfish (Pangasianodon hypophthalmus) Infected with Aeromonas hydrophila - Windarti Windarti; Irwan Effendi; Ronal Kurniawan; Mega Novia Putri; Dimas Gusriansyah; Okta Rizal Karsih (Jurnal Natur Indonesia, 2024)
Moringa leaves can be used as an herbal plant in fish growth to prevent and treat bacterial infections. This study aims to determine the effect of fermented moringa leaves through feed on blood glucose in striped catfish (Pangasianodon hypophthalmus). This research was conducted from September to November 2023 at the Marine Biotechnology Laboratory, Faculty of Fisheries and Marine Sciences, Riau University. The method used is an experimental method using a completely randomized design with 4 (four) treatments and 3 (three) replicates; the treatment dose of fermented moringa leaves is T0 (control), T1 (10 g/kg feed), T2 (15 g/kg feed), and P3 (20 g/kg feed). The catfish measured 5.00 ± 1.00 cm and weighed 4.00 ± 0.50 g, reared in an 80 L tank at a stocking density of 1 fish / 4 L water. The maintenance was carried out for 60 days, and blood glucose observations were made at the beginning (H-1), day 30 (H-30), day 60 (H-60), and post-challenge test (H-75). The results showed that adding fermented moringa leaves to the diet did not affect the blood glucose of the catfish (p>0.05). This indicates that moringa leaves can keep the fish in normal condition after being challenged with Aeromonas hydrophila bacteria.